2019
DOI: 10.15452/cejnm.2019.10.0024
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the principles of the perioperative safety process in the context of the work of perioperative nurses

Abstract: Aim: The main aim was to describe the current state of perioperative safety processes with reference to perioperative nurses' work. Design: To achieve the stated goal, a custom-built "ad hocˮ research design was created, using a combination of qualitative and quantitative methods. The findings of the exploratory qualitative survey were verified by the quantitative survey focused on in this article. Methods: The exploratory survey and Surgical Safety Checklist were the basis for a questionnaire which was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
2
1
2
Order By: Relevance
“…This implies that nursing experience is more likely to affect compliance with PPCG. However, these findings are contrary to a study carried out in Taiwan whereby a nationwide study in various recognized clinics showed that PPCG were not utilized by nurses with an experience of 15 years and above [9]. The study results also showed that male nurses were 85.1% [OR=0.149 CI 95% (0.063-0.353) p=<0.001], less likely to be non-compliant to PPCG.…”
Section: Discussioncontrasting
confidence: 94%
“…This implies that nursing experience is more likely to affect compliance with PPCG. However, these findings are contrary to a study carried out in Taiwan whereby a nationwide study in various recognized clinics showed that PPCG were not utilized by nurses with an experience of 15 years and above [9]. The study results also showed that male nurses were 85.1% [OR=0.149 CI 95% (0.063-0.353) p=<0.001], less likely to be non-compliant to PPCG.…”
Section: Discussioncontrasting
confidence: 94%
“…Na síntese de dados dos estudos incluídos na revisão, constatou-se que eles enfocaram três grupos de práticas assistenciais que a enfermagem pode realizar a fim de promover a segurança do paciente, a saber: aplicar a lista de verificação de segurança em cirurgia (LVSC) [9][10][11] ; usar escala preditiva a formação de LP 12 ; e planejar a assistência com recurso a protocolos 13,14 .…”
Section: Resultsunclassified
“…Intraoperative patient safety is concomitant with physical, intellectual, and professional challenges (Pavlová, Holá & Škaroupková 2019 :1125). Intraoperative teams are aware of the risks and benefits associated with the use of the WHO SSC for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative patient safety is concomitant with physical, intellectual, and professional challenges (Pavlová, Holá & Škaroupková 2019:1125 of the WHO SSC and its benefits, if they do not know the actual tool and cannot apply it, the effort will be futile. Increased intraoperative safety risks and reduced operational efficiency are caused by ignorance of the benefits of the use of the WHO SSC (Greig, Maloney & Higham 2020:304).…”
Section: Discussionmentioning
confidence: 99%